Developing the teacher's social competency assessment instrument in the fourth industrial revolution era - Rusijono Rusijono; Amat Jaedun; Badrun Kartowagiran; Ahman Ahman; Lukman A. R. Laliyo; Socheath Mam (Jurnal Penelitian dan Evaluasi Pendidikan, 2020)
The purpose of the study was to develop instruments for measuring teacher candidates' social competence in the Fourth Industrial Revolution (the fourth I.R.) era. The instrument was developed by referring to Indonesian Law Number 14 of 2005 concerning Teachers and Lecturers and the Regulation of the Minister of National Education Number 16 of 2007 to strengthen some special competence of teacher candidates in the fourth IR era. Limited instrument testing was carried out to 107 test subjects for the 6th-semester undergraduate education program at Yogyakarta State University, consisting of three study programs: Mathematics Education, Indonesian Language Education, and English Language Education study programs. The results of the content validity analysis of 30 instrument items obtained the Aiken V index between 0.61 - 0.93, with 29 items valid, and one invalid item. The construct validity analysis with EFA showed 25 valid items and five invalid items, with a KMO value of 0.504. The significance of Bartlett's test was p = 0.000. Meanwhile, the construct validity analysis with CFA showed the model fit, with a Chi-Square value = 290.35 (p 0.05). The reliability results show that the Cronbach’s Alpha coefficient is 0.40 (moderate category). This shows that the social competency assessment instruments for teacher candidates in the fourth IR era developed are feasible to use, with several improvements.